Evaluation of postharvest physiological deterioration in storage roots of cassava (Manihot esculenta) genotypes - RAJU, SARAVANAN; STEPHEN, ROY; RAVI, VELUMANI; NEELAKANTAN, SHEELA MADHAVI; MAKASANA, JAYANTIKUMAR; CHAKRABARTI, SWARUP KUMAR (The Indian Journal of Agricultural Sciences, 2015)
Cassava (Manihot esculenta Crantz) is an important tropical root crop grown worldwide for food, feed and industrial purposes. Harvested cassava roots quickly deteriorate and loose the shelf-life due to a phenomenon called postharvest physiological deterioration (PPD). PPD symptom starts within 24 hr after harvest, initially as blue black discolouration in the storage parenchyma and quickly spread to entire root. The roots become unfit for consumption within 2-3 days after the harvest in most cases. Identification of delayed PPD genotypes in cassava will help breed superior varieties tolerant to deterioration with long shelf-life. Low molecular weight phytochemicals produced during PPD are reported to have significant role in PPD development. We analyzed the biochemical changes associated to secondary metabolites in 61 cassava genotypes during storage and evaluated the relationship with PPD. PPD evaluation was done visually at specified intervals by taking transverse sections at 25, 50 and 75% along length of roots from proximal to distal end and the roots were categorized into different PPD classes based on the visual scoring. Root morphological, starch, and carotene content had no direct correlation with PPD. The HPTLC chromatographic data on phytoconstituents of methanolic extract of cassava roots and its relation with PPD symptoms were analyzed and polymorphic bands were assessed for grouping the genotypes based on PPD expression levels. Cluster analysis revealed a close association between PPD expression and phytochemical constituents of stored roots and this can help to categorize the genotypes based on PPD.